Racial hygiene: Medecine under the Nazis - Proctor, Robert (Harvard Univ. Press, 1988)
The book presents the most comprehensive account to date of Germany medical involvement in the sterilization and castration laws, the laws banning marriage between Jews and non-Jews, and the massive program to destroy "lives not worth living". the book demonstrates that the common picture of a passive scientific community coerced into cooperation with the Naziz fails to graps the reality of what actually happened - namely, that many of the political initiatives of the Naziz arose from within the scientific community, and that medical scientists actively designed and administrated key elements of National Socialist policy